Movable Asset Management In West Pilohayanga Village, Telaga District, Gorontalo Regency - Suprapto, Srihandayani; Pakudu, Robin; Kadir, Septian (Institut Manajemen Wiyata Indonesia, 2024)
This study aims to find out how the Management of Mobile Assets in West Pilohayanga Village, Telaga District, Gorontalo Regency. The research method uses a qualitative approach with a descriptive type of research. The results of the study found that the Management of Movable Assets in West Pilohayanga Village, Telaga District, Gorontalo Regency has not fully run well. This is when viewed from 4 (four) indicators of asset management, all of these indicators have not run well. In the planning indicator, it was found that the planning process carried out in asset management was not fully attended by the community in general, who attended indicated that people who had close ties with village leaders. Utilization indicators, it is found that not all people who can utilize these movable assets because in the lending process sometimes do not get loans. Monitoring and evaluation indicators were not carried out properly by the village government, besides that monitoring was carried out but was not accompanied by clear records. Furthermore, related to the control and supervision indicators, it was found that movable assets owned by the village were not always carried out properly supervised.